Literature Review: Evaluation of the Use of Tonsillectomy as a Surgical Intervention in Patients with Recurrent Tonsillitis - Risna Risna; Reza Zainal Abidin; Amsyar Akil (Newinera Publisher, 2026)
Recurrent tonsillitis is one of the most common diagnoses in ENT practice that significantly impacts patients' quality of life. Although antibiotic therapy is the first line of treatment, persistent infection often requires surgical intervention. This study aims to evaluate the clinical efficacy, impact on quality of life, and pharmacoeconomic aspects of tonsillectomy compared to conservative management. The method used was a narrative systematic review of international literature from 2016 to 2025 obtained from Google Scholar, PubMed, and NCBI. The results of the search of 17 selected articles showed that tonsillectomy significantly reduced the frequency of sore throat episodes and antibiotic use compared to medical therapy. The use of modern techniques such as Coblation has been shown to reduce postoperative pain and accelerate recovery compared to conventional techniques. In addition, tonsillectomy provides significant long-term improvements in quality of life, both physically and mentally. In conclusion, tonsillectomy is an effective, safe, and cost-efficient surgical procedure for patients with recurrent tonsillitis, with strict indications to optimize clinical outcomes.